Optimality conditions for asymptotically stable impulsive control systems - Fernando Lobo Pereira (2008)
We consider an infinite horizon optimal impulsive control problems for which a performance criteria is minimized by choosing asymptotically stable control strategies. We present necessary optimality conditions in the form of a maximum principle and show how they can be derived from an auxiliary conventional (nonimpulsive) optimal control problem. As far as we know, results of this kind have not been previously derived for problems with trajectories restricted to the set of stabilizing ones.